Diagnostic Hierarchy of Tic Disorders in Real-World Clinical Practice - Sung, Yeeji; Hong, Soon-Beom (Journal of the Korean Academy of Child and Adolescent Psychiatry, 2023)
According to the 10th revision of the International Classification of Diseases, the main categories of tic disorders (F95.0, F95.1, and F95.2) follow a diagnostic hierarchy based on the duration and diversity of tic symptoms. The present study investigated the use of this diagnostic hierarchy in real-world clinical practice. Based on the National Health Insurance Service-National Health Information Database, the diagnosis of transient tic disorder (F95.0) made after a diagnosis of chronic motor or vocal tic disorder (F95.1) or Tourette's syndrome (F95.2) and diagnosis of chronic motor or vocal tic disorder (F95.1) made after a diagnosis of Tourette's syndrome (F95.2) were referred to as type A errors. The diagnosis of transient tic disorder (F95.0) repeated after a period of >12 months was referred to as type B error. Demographic and clinical differences according to the diagnostic error types were analyzed using analysis of variance, Student's t-tests, and chi-squared tests. Most participants (96.5%) were without errors in the diagnosis of tic disorders. Higher proportions of males (p=0.005) and antipsychotic prescriptions (p<0.001) were observed in patients with type A or B diagnostic errors. A higher proportion of health insurance holders was observed among those with type A errors (p=0.027). Errors were absent in majority of the tic diagnoses in real-world clinical practice in terms of the diagnostic hierarchy.